Isolation and Identification of Polyphenols From Fresh Sweet Sorghum Stems and Their Antibacterial Mechanism Against Foodborne Pathogens - Chen, Hao; Xu, Yifei; Chen, Haoyu; Liu, Hao; Yu, Qunli; Han, Ling (Frontiers in Bioengineering and Biotechnology, 2022)
Fresh sweet sorghum stalks contain many natural ingredients, which have certain antioxidant properties and can significantly inhibit the growth of foodborne pathogens. In this study, the content of polyphenols in fresh sweet sorghum stalks was 5.77 mg/g after process optimization with 18 types of phenolic acid identified. Polyphenol extracts in sweet sorghum are antibacterial to Staphylococcus aureus, Escherichia coli, Listeria sp., and Salmonella sp., and the antibacterial effect on Gram-positive bacteria was greater than that on Gram-negative bacteria. The extract has a total antioxidant capacity of 9.4 μ mol Trolox/mL, and the polyphenol extract of the sweet sorghum can increase the conductivity of cell suspension by destroying the membrane structure, resulting in cell electrolyte leakage. Our study thus provided an optimal process to extract polyphenols from sweet sorghum stalks, the methodology to identify the major components within the extract, and a new direction for the comprehensive utilization of fresh sweet sorghum stalks. In addition, the mechanism of antibacterial activities of the active extract of sweet sorghum was proposed through destroying cell membrane proteins, leading to the changes in bacterial morphology and internal structure.